A Sustainable Bioleaching of a Low-Grade Chalcopyrite Ore - Velasquez-Yevenes, L (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This paper reports on a study of column bioleaching of a low-grade chalcopyrite ore that is currently dump-leached under natural biological conditions without any control over microbial populations. The experimental methodology was focused on the effect of managing the bacterial populations in a raffinate solution sourced from a dump-leach operation. This study presents results from columns of two heights (0.45 and 1.0 m). We demonstrated that intermittent irrigation enhanced the chalcopyrite dissolution during column leaching, but excessively long rest periods negatively affected the chemical and bacterial activity due to the shortage of oxidizing agents and/or nutrients for microorganisms. The recovery of low-grade chalcopyrite ore was enhanced by increasing the microbial cell density. The addition of 1.5 × 108 cells/mL to the 0.45 m column and 5.0 × 107 cells/mL to the 1 m column resulted in increased extraction, with the copper dissolution increasing from 32% to 44% in the 0.45 m column and from 30% to 40% in the 1.0 m column over 70 days of leaching. Under these conditions, the pH level remained constant at ~1.8, and the redox potential was around 840 mV vs. the SHE throughout the experiment. These results provided useful insights for evaluating a sustainable controlled dump-based technology for mineral bioprocessing. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.